2017
DOI: 10.11604/pamj.2017.28.150.13159
|View full text |Cite
|
Sign up to set email alerts
|

Newborn haemorrhagic disorders: about 30 cases

Abstract: The haemorrhagic disorders are particularly frequent in neonatal period. Their causes are varied and their knowledge is capital for their good management. Our purpose was to describe the epidemiological, diagnostic, and common causes of new-bornhaemorrhagic syndrome in paediatric emergency medical department of the Rabat Children's Hospital. We conducted a descriptive study from December 2015 to April 2016, about new-borns admitted to medical emergencies for haemorrhagic syndrome defined by bleeding, exteriori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
8
1
1
Order By: Relevance
“…In the study population, hypoglycemia was reported in 4.3% and the presence of infection was reported in 2.0%, both comparable with the general population (5-15% and 4% respectively 24,25 ). The occurrence of bleeding diathesis and encephalopathy in our study population were 8.1% and 3.9% respectively, thus higher than in the general population (2.17-5.9% and 0.3% respectively 26,27 ). The data of this study showed that in 7 of the 47 patients (14.9%) with follow-up, cognitive, and/or motor developmental delay was reported.…”
Section: Phenotypic Spectrumcontrasting
confidence: 57%
“…In the study population, hypoglycemia was reported in 4.3% and the presence of infection was reported in 2.0%, both comparable with the general population (5-15% and 4% respectively 24,25 ). The occurrence of bleeding diathesis and encephalopathy in our study population were 8.1% and 3.9% respectively, thus higher than in the general population (2.17-5.9% and 0.3% respectively 26,27 ). The data of this study showed that in 7 of the 47 patients (14.9%) with follow-up, cognitive, and/or motor developmental delay was reported.…”
Section: Phenotypic Spectrumcontrasting
confidence: 57%
“…Thus, protocols for stabilisation and direct transfers need to be explored to save time [49]. It is unfortunate that one of the children who presented with bleeding after circumcision died since the condition can be prevented by ensuring that all babies, especially those born in the community, receive vitamin K and are treated with blood transfusion if necessary, though other causes of bleeding in the newborn need to be excluded [18,50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another cause of seepage could be coagulation disorder occasionally found among neonates [59]. The excessive seepage that was observed only in a few bodies after MITS could also be due to limited concentrations of coagulation proteins in the deceased [59,60]. The seepage could be interpreted as the unintended consequences of purposive social actions [39].…”
Section: Discussionmentioning
confidence: 99%